Elements of Digital Citizenship within Surabaya City Text in New Media - Zudan Rosyidi (k@ta: A Biannual Publication on the Study of Languange and Literature, 2024)
This article identifies digital citizenship texts on the web www.c2o-libarary.net. These texts are analyzed using the concept of digital citizenship which was conceptualized by Westheimer and Kahne (2004), namely “personally responsible citizens”, “participatory citizens”, and “justice-oriented citizens”. These digital citizenship texts are narratives about individual and community activism in cyberspace which are uploaded via www.c2o-libarary.net. Each subject of the author tries to construct activism as a form of critically disseminating information and knowledge to other communities but with a narrative that is easy to understand and digest. The writer's knowledge and interaction in the Surabaya space is a determining factor in the narratives that are published in the media. In the end, the published narrative becomes a collection of concepts and ideas that can guide the government and the people of Surabaya to move forward and better life.